Partnerstwo publiczno-prywatne jako forma realizacji inwestycji infrastrukturalnych w gminie na przykładzie gmin województwa łódzkiego - Nowak, Magdalena (Public-Private Partnership as a Form of Realizing Communal Infrastructure Investment on the Example of the Communes from Łódź Region, 2008)
Communal technical infrastructure is not enough developed to satisfy citizens' and entrepreneurs' needs. Thus, there is a need to find a solution which would be effective in terms of its development. Public-private partnership could be an answer, but, nevertheless there are many barriers, for ample law regulations, which limit its implementation. This paper presents major advantages of partnership, as well as the identified barriers of its use. The article is based on the research executed within communes of Łódź voivodship. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 431-439